Peran Guru Dalam Pengelolaan Kelas Terhadap Hasil Belajar Siswa Sekolah Dasar - Asratu Aini; Alfan Hadi (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Amin, 2023)
This study aims to determine how teachers manage the classroom to create optimal learning conditions for elementary school students at MI Attarbiyah Addiniyah Al-Amin Gersik West Lombok in grade 5. The research method used is a case study with a qualitative approach. The research subjects were three elementary school teachers who differed in terms of background, experience, and teaching style. Data were collected through observation, interviews, and documentation. Data analysis was conducted using data reduction, data presentation, and conclusion drawing techniques. The results showed that based on the results of the study, the following conclusions can be drawn: the role of teachers in classroom management on the learning outcomes of elementary school students includes learning strategies, habituation, exemplary, reinforcement, and extracurricular activities.